Os significados do não crescimento em porte: um estudo com micro e pequenas empresas de Curitiba - Souza, Ricardo Rodrigues de (2014)
A major characteristic of modern capitalist society is the idea of progress and development by the means of economic growth (Victor, 2008; Esteva, 2010). In this context, business growth has been typically equated to management success (Baum, Locke & Smith, 2001). Notably, in management and organization studies several theories aiming to contribute to business growth have been proposed (see for example Storey, 1994). Beyond that, government policies have been usually developed with similar purpose. In Brazil, an emerging market eagerly to grow, the Growth Acceleration Program (Programa de Aceleração do Crescimento - PAC), initiated under President Luis Inacio Lula da Silva in 2007, is a typical example of such policies. The pursuit of growth has also received the support of numerous entrepreneurial agencies, mainly focused on small business development. Not to mention, the financial banking system, which has been established as a powerful institution for growth. In this context, not growing is hardly seen as an alternative. Developing a critical perspective on the topic, Seifert and Vizeu (2011) argue that organizational growth has became a management ideology, and that despite being dominant in modern society, one should not forget that many business organizations voluntarily choose not to growth. In this study we explore the meanings that owners of micro and small business with more than 30 years of operation attach to the fact that their business have not grown. We develop an interpretative perspective, which considers the role of meanings and interpretation as key to understand the choices and actions of organizations (Daft & Weick, 1984), Methodologicaly we conducted seven qualitative interviews with the owners of micro and small business located in the city of Curitiba, Brazil. Our findinds suggests that understanding the alternative of not growing is a complex issue. More specifically, we identified 10 categories of meaning informing entrepreneur’s interpretation regarding the fact that their business have not grown, namely: i) conservadorism (e.g.: aversion to take risks); ii) need for keeping traditional characteristics of the business; iii) maitaining control; iv) success beyond growth; v) growth is not necessary for survival; vi) not growing is a choice; vii) pain; viii) comfort zone; ix) biological life; x) failure. Although some of these categories of meanigng have been already idetified in the specilizaled literature, some of them are new and inform newer ways of understanding the alternative of not growing. Our findings further suggest that although in some cases the absence of growth can be understood as a failure, in others, the meanigns given by owners of smaller business support interpretative schemes that function as self-imposed limits to growth. Moreover, our findings challenge the idea that growth is the only alternative for survival in competitive markets. It thus supports the argument of Seifert and Vizeu (2011) that organizational growth has indeed became a management ideology. It is our intention that this research, despite its own limitations, will contribute to fuel debate and furhter resarch on whether business growth is rather a necessity as it is typicaly portryaind in mainstream literature, or a mere alternative.